The Influence of Job Rotation, POS, and CDO on Turnover Intention: The Mediating Role of Job Satisfaction at KPP Pratama Tanjung - Rahmatullah, Afrinanda; Sultan, Zulkifli; Budi Abadi, Yudha (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This study aims to examine the effect of job rotation, Perceived Organizational Support (POS), and Career Development Opportunities (CDO) on turnover intention with job satisfaction as a mediator among employees of KPP Pratama Tanjung. The novelty of this research lies in the integration of the Job Demands-Resources (JD-R) theory with the concept of external employability within the civil servant context. Using an explanatory quantitative approach, data were collected via saturated sampling from 42 executive employees. Data analysis was conducted using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with WarpPLS 8.0. The results showed that job rotation acts as a job demand which significantly increases turnover intention (β = 0.39, p < 0.001). Interestingly, job satisfaction positively correlated with turnover intention (β = 0.33, p < 0.001), confirming the phenomenon of external employability. POS (β = 0.04) and CDO (β = 0.02) had no significant effect. The mediation test proved that job satisfaction does not mediate the effect of the three independent variables on turnover intention. The practical implication urges the institution to evaluate and redesign more participative rotation policies to mitigate the risk of core competency retention.